PENGARUH KEPEMIMPINAN, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA PT. ANGKASA PURA 1 DIVISI KOMERSIAL - putra anteja, i gusti ngurah agung (E-Jurnal Manajemen, 2014)
Efficacy of company in giving service to consumer very determined by human resource had. reliable human resource have ability, skillful, and high loyalitas to each duty area, so that they earn to execute duty very seriously and full of responsibility and also have the spirit of and job of loyalitas high to company Target of this research is to know influence of leadership, communications, and environment work to spirit of job at PT. Ankasa Gate 1 Commercial Division of Bali. By using counted 32 respoden, data-processing use doubled regresi with test of f test and of t. Pursuant to result of analysis found that leadership, environment and communications work by simultan have an effect on signifikan to spirit of officer job. Leadership, environment and communications work by parsial have an effect on signifikan to spirit of officer job. Leadership variable have an effect on dominant to spirit of  job at PT. Space Gate 1Divisi is Commercial of Bali. Suggestion the given is to revise leadership and give coherent sanction to officer doing collision, intensifying open communications between subordinate and head, re-arranging balmy work path and hygiene of job environment   Keyword: Leadership, Communications, Environmental of Job, Spirit of job
Keywords: Kepemimpinan; Komunikasi; Lingkungan Kerja; Semangat kerja